INFLUENCE OF FISCAL STRESS AND LEGISLATURE SIZE ON EXPENDITURE CHANGE - Ifa Ratifah; Peni Nuraeni (JRAK, 2021)
The study aims to examine and analyze the effect of fiscal stress and legislative size on expenditure change in the district or city of West Java Province. The research method used is descriptive method and verification method. Data collection techniques are carried out through secondary data obtained from Supreme Audit Istitution (BPK). The population of this study is all regencies and cities in West Java Province in the 2016-2018 fiscal year. The number of regencies and cities in West Java Province in the 2016-2018 fiscal year was 27. This research sample selection method uses Non Probability Sampling using saturated sampling with a total of 81 districts and cities. The results showed that fiscal stress negatively affected expenditure change, while the influence of the legislature size had a positive effect on expenditure change.